FDI and tourism : the development dimension : East and Southern Africa (UN New YorkUS, 2008)
Highlights the main findings with respect to the development impacts TFDI in five East and Southern African countries on income, employment, technology and skills transfer, wages and linkages, as well as the social and environmental impacts among others. Examines the salient policies that are in place. Identifies those that have hindered and promoted a TFDI.
Keywords: FOREIGN INVESTMENT